2017
DOI: 10.1111/jfpp.13218
|View full text |Cite
|
Sign up to set email alerts
|

Active biodegradable film with encapsulated anthocyanins: Effect on the quality attributes of extra-virgin olive oil during storage

Abstract: The aim of this study was to verify the effectiveness of an active biodegradable film on the maintenance of extra‐virgin olive oil (EVOO) quality attributes. Level of peroxides, acidity, K232, color, chlorophylls, and carotenoids were determined as parameters to verify the oil quality over storage period. Maltodextrin was used to encapsulate anthocyanins and was the major component in the films, which were used as pouches to pack the oil. The samples were stored at 40°C, exposed to fluorescent light, and monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 33 publications
(53 reference statements)
3
30
0
Order By: Relevance
“…The primary oxidation of sunflower oil was retarded by GCR‐based films in comparison with oil packed in transparent polyethylene terephthalate (PET) bottles and unpacked, as assayed by peroxide value during 28‐35 days under accelerated conditions . Starch‐based film incorporated with encapsulated anthocyanins were effective on protecting EVOO from oxidation under accelerated conditions . It was found that the biodegradable films maintained PV values under the limit up to Day 8 (13.6 mEq/kg), whereas EVOO packed in PP was deteriorated before Day 4 (326.5 mEq/kg).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary oxidation of sunflower oil was retarded by GCR‐based films in comparison with oil packed in transparent polyethylene terephthalate (PET) bottles and unpacked, as assayed by peroxide value during 28‐35 days under accelerated conditions . Starch‐based film incorporated with encapsulated anthocyanins were effective on protecting EVOO from oxidation under accelerated conditions . It was found that the biodegradable films maintained PV values under the limit up to Day 8 (13.6 mEq/kg), whereas EVOO packed in PP was deteriorated before Day 4 (326.5 mEq/kg).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of GCR‐GEN films on maintaining the quality attributes of EVOO under accelerated storage conditions was investigated following the methodology described by Stoll et al with some modifications. Films were produced to develop EVOO sachets designed for single use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] With respect to administration, especially to the human body,i deally such capsules should be fabricated based on ab iocompatibleb iodegradablep olymer consisting of an amphiphilic backbonet hat gives the possibility to bind equally efficiently to the hydrophobic core and cover it but also to have ah igh affinity to water. [42,43] The active releasek inetics should ideally be constant. However, zeroth-order kinetics are seldom obtained, whereas first-order release is the rule.…”
Section: Resultsmentioning
confidence: 99%